Redundancy, Scale and Duplicity in the Administration: a Critique of the Myths about the Administrative Rationality in the Proposals of the Public Administration Reform in Spain - Bastos Boubeta, Miguel Anxo (Revista del CLAD Reforma y Democracia, 2016)
This text tries to criticize the administrative principles that inspire good part of the projects of administrative reform initiated in the last years. In spite of the fact that they have been academically discussed for several decades, they are still presents in the political and administrative discourse. We understand that concepts like redundancy, scale or efficiency are not valid like they are usually understood and they are used often of incorrect form in the public area. We want to elaborate therefore a theory on these concepts and to discuss his possibility of adjustment to the public administration, especially Spanish.